Edo influence on Santome: evidence from verb serialisation - Hagemeijer, Tjerk (2011)
Ferraz (1979) convincingly shows the impact of two typologically distinct African strata in the making of Santome: È dó and Kikongo. In this paper, it will be shown that the extensive verb serialisation found in Santome shows a significant amount of typological overlap with È dó multi-event and compound verb constructions. Since the impact of È dó on Santome goes clearly beyond verb serialisation and is also found in the other Gulf of Guinea creoles, the findings strongly suggest an early È dó founder impact in detriment of Kikongo or Bantu in general .